PS 15-23 CERTIFICATE COURSE IN MANAGEMENT OF HYPERTENSION: AN INNOVATIVE CAPACITY BUILDING MODEL FOR PRIMARY CARE PHYSICIANS (PCPs) IN INDIA. (September 2016) - Jose, Arun; Bhalla, Sandeep; Roy, Ambuj; Vats, Shivangi; Sharma, Anshika; Pandey, Nikki; Poulter, Neil; Padmanabhan, Sandosh; Prabhakaran, Dorairaj
Abstract : Objective: Develop and deploy a novel multiple stakeholder model for capacity building to enhance knowledge, skills and core competencies of PCPs in the management of hypertension. Design and Method: A partnership between the Public Health Foundation of India, International Society of Hypertension, British Hypertension Society and Centre for Chronic Disease Control was developed to design a countrywide course for PCPs. This partnership brought together public health experts in India to manage the logistics and delivery of the programme on a country wide basis and develop the curriculum with advice and oversight from international hypertension societies. Results: Twenty five regional centers in 14 states of India have been identified for the implementation of the program with a cardiologist/medicine specialist as the faculty for each centre. The faculty will be trained by a panel of national experts on the course curriculum that has been formulated by the partners. The course will be delivered as monthly modules over 10 months with integrated monitoring and evaluation. The program is expected to train 1000 PCPs over a period of two years. Conclusions: A partnership model for capacity building has been designed to train PCPs in the effective management of hypertension with enormous potential for reducing the burden and mortality associated with raised blood pressure.